2013
DOI: 10.1523/jneurosci.5723-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Lateral and Medial Intraparietal Areas during a Visual Categorization Task

Abstract: Categorization is essential for interpreting sensory stimuli and guiding our actions. Recent studies have revealed robust neuronal category representations in the lateral intraparietal area (LIP). Here, we examine the specialization of LIP for categorization and the roles of other parietal areas by comparing LIP and the medial intraparietal area (MIP) during a visual categorization task. MIP is involved in goal-directed arm movements and visuomotor coordination but has not been implicated in non-motor cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 39 publications
6
40
0
Order By: Relevance
“…Previous studies showed that firing rates of LIP and PFC neurons are markedly tuned to the learned stimulus categories, although the strengths and latencies of categorical signals may differ across areas (Freedman and Assad, 2006; Swaminathan and Freedman, 2012; Swaminathan et al, 2013). The broad similarity in category-related responses suggest that they play overlapping roles in solving the DMC task (Goodwin et al, 2012; Merchant et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that firing rates of LIP and PFC neurons are markedly tuned to the learned stimulus categories, although the strengths and latencies of categorical signals may differ across areas (Freedman and Assad, 2006; Swaminathan and Freedman, 2012; Swaminathan et al, 2013). The broad similarity in category-related responses suggest that they play overlapping roles in solving the DMC task (Goodwin et al, 2012; Merchant et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…As in a previous study, we employed two specialized SVM classifiers 22 designed to independently assess direction and category selectivity (see Methods and Fig. 4a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed methods used in this study have been described in previously 22,28 , and are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations